2022
DOI: 10.3390/ijms23147937
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Cytokine Profiling of Patients with COVID-19 Receiving Tocilizumab Therapy

Abstract: Coronavirus disease 2019 (COVID-19) is characterized by immune activation in response to viral spread, in severe cases leading to the development of cytokine storm syndrome (CSS) and increased mortality. Despite its importance in prognosis, the pathophysiological mechanisms of CSS in COVID-19 remain to be defined. Towards this goal, we analyzed cytokine profiles and their interrelation in regard to anti-cytokine treatment with tocilizumab in 98 hospitalized patients with COVID-19. We performed a multiplex meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…Remarkably, the elevation in the expression of these molecules closely paralleled the clinical observations concerning COVID-19 patients 28 . For instance, Lebedeva et al 29 conducted a comprehensive cytokine profiling of COVID-19 patients undergoing Tocilizumab therapy, uncovering statistically significant differences in normalized mRNA fluorescence values for IL-6, IL-1RA, IL-10, and G-CSF between patients with and without clinical endpoints.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, the elevation in the expression of these molecules closely paralleled the clinical observations concerning COVID-19 patients 28 . For instance, Lebedeva et al 29 conducted a comprehensive cytokine profiling of COVID-19 patients undergoing Tocilizumab therapy, uncovering statistically significant differences in normalized mRNA fluorescence values for IL-6, IL-1RA, IL-10, and G-CSF between patients with and without clinical endpoints.…”
Section: Resultsmentioning
confidence: 99%
“…However, the study concluded that the cytokine storm reflected by the increased release of cytokines did not correlate with the standard parameters of disease severity. 8 Age, one of the comorbidities of COVID-19 was found to be associated with cytokine signatures in COVID-19 patients. IL-8, IL-10, IL-15, IL-27, and TNF-α levels correlated with older age, longer duration of hospitalization, and severity of the disease in patients with COVID-19.…”
Section: Introductionmentioning
confidence: 93%